Identification of games and sex-related activity profile in junior international badminton - Rojas-Valverde, D.; Gómez-Carmona, C. D.; Fernández-Fernández, J.; Garcia-López, J.; Garcia-Tormo, V.; Cabello-Manrique, D.; Pino-Ortega, J. (International Journal of Performance Analysis in Sport, 2020)
The aims of the present study were (a) to analyse the activity profile in U`18 Badminton players during an international tournament and (b) to compare the games and sex-related differences. Twenty-four players (women = 14; men = 10) were assessed using inertial measurement units with ultra-wideband indoor tracking system. Eleven variables were extracted after principal component analysis (PCA). Differences between games and gender were performed by mixed analysis of variance. In men, PCA of the whole game explained 89.2% and in women 75.7%. The most representative variables in men`s and women`s were relative distance and maximum accelerations (PC1). The players` activity profile was (men vs women) 44.6 ± 3.8 vs 43.5 ± 5.2 m/min in relative distance, 25.9 ± 1.9 vs 24.7 ± 1.9 n/min in relative acceleration, 3.87 ± 0.3 vs 3.47 ± 0.4 m/s2 in maximum acceleration, 175.5 ± 9.4 vs 173.2 ± 15.6 bpm in average heart rate. Sex-related differences were found in maximum accelerations (p < 0.01) and relative accelerations (p < 0.01) and in relative distance by games. The workload dynamics during games and between sexes should be addressed by team staff in order to develop effective tactical and recovery strategies during badminton tournaments.